Pattern of Valvular Involvement and Demographic Features of Patients on Injection Benzathine Penicillin at Dhulikhel Hospital - Humagain, S; Gurung, R; Pant, P; Koju, R; Bedi, TRS (Nepalese Heart Journal, 2013)
Background Rheumatic heart disease (RHD) is the most common cardiovascular disease in children and young adults. Though declined and almost non-existent in developed nations, RHD is still one of the leading cause for premature death and disability in developing countries. Prevalence of RHD is high in both rural as well as urban area of Nepal. Present study is designed to look at the pattern of valvular involvement and demographic features in RHD. Methods 326 Patients indicated for inj. Benzathine penicillin were selected and echocardiograph performed to see the pattern of vavular involvement. Data analysis was done using SPSS 17. Result The most common type of lesion was mixed type with mitral valve involvement. MR was the most common isolated lesion. MS was more commonly seen in females whereas AS was more common in males. Secondary prophylaxis was more common than primary prophylaxis. Conclusion RHD still being a major problem and a preventable disease so extensive screening program is required to identify them early and prevent the complication. DOI: http://dx.doi.org/10.3126/njh.v9i1.8342 Nepalese Heart Journal Vol.9(1) 2012 pp.16-19